Neuropsychological mechanisms and causes of neurotisation in preschool children - FISYNA, Nadiya (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Background. The relevance and purpose of the study are determined by the high frequency of manifestations of children’s mental health disorders, such as neuropsychiatric disorders, increased anxiety, fear, self-doubt, excessive vulnerability, etc. An open-armed conflict brings the problem of mental disorders in children to the fore. Since the war is the most frustrating period, it contributes to the development of a large number of problems in the emotional sphere, among the dysfunctions of which the pre-neurotic disorders with the subsequent transition to neurotization are most manifested. The article aims to analyze the neuropsychological mechanisms and causes of emotional disturbances in preschool children to determine the criteria and factors of pre-neurotic disorders. Methods. Abstraction, analysis, and synthesis were chosen as research methods, which allowed the topic to be revealed both in historical chronology and in the current time at the theoretical and methodological levels. For qualitative analysis, the topic was divided into micro-levels, which made it possible to examine its structure in detail, carry out an in-depth historical analysis of the views of scientists, and investigate historical changes in the level and depth of knowledge related to the issue of emotional disorders in preschool children Results. In the course of the conducted research, the theoretical basis of the study of emotional disorders was clarified, the localization of emotional processes in brain structures was considered, and the causes of emotional disorders and distortions were formed. Classifications and criteria of emotional and behavioral disorders are determined. The term "pre-neurotic disorder" is defined as a type of emotional disorder, its symptoms and its difference from neurosis are characterized. Critical age periods and factors that provoke the appearance of pre-neurotic disorders have been determined Conclusions. The issue of studying the problems of the emotional-volitional sphere is quite controversial today, causing discussions that touch not only psychological and pedagogical sciences but also neurobiology, sociology, cultural studies, ethnology, etc. This type of disorder is challenging to diagnose because behavioral disorders can be a manifestation of the child’s individual characteristics, age norms, one-time temporary behavior, etc. That is why it is essential to pay a high level of attention to the differential diagnosis of emotional disorders and, in particular, pre-neurotic disorders in preschoolers.